Otraženije isihastskih idej v sozdanii obraza svjatogo (Na materiale drevnerusskoj agiografii) - Vidmarović, Natalija (1998)
The theoretical justification of Hesychasm was preceded by a long period of spiritual practice by ascetics, a period of accumulation of mystic experience in Ťobtaining God, s blessingť which found its reflection in the hagiographic works. Adopting the Byzantine theological literature, the Slav men of letters also accepted the particular type of world outlook based on the firmly established Hesychastic traditions. The ideas of the Hesychasts were reflected in the hagiographic works, in the description of all the stages of the spiritual and physical transformation of the saint, the so-called deification of his personality. In the article is analysed the attempt to convey by the word the duality (the earthly and heavenly nature of the saint) which led to countless verbal variations corresponding to the Hesychastic notions of the hidden meaning of the word as one of the divine energies associated with the ideas of Dionysius the Areopagite about the Ťcontractionť and Ťexpansionť of the word in the movement towards the sensual, the earthly, and vice versa towards the heavenly sphere. In this way the influence of Hesychasm was felt also in the approach of the hagiographer to the solution of the problem of the impossibility in principle to represent the ideal object the saint by the means of material language.
Projekt MZOS
RUS